2020
DOI: 10.3390/molecules25030580
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Beta Peptides Trigger Aggregation of Alpha-Synuclein In Vitro

Abstract: Alzheimer’s disease (AD) and Parkinson’s disease (PD), including dementia with Lewy bodies (DLB), account for the majority of dementia cases worldwide. Interestingly, a significant number of patients have clinical and neuropathological features of both AD and PD, i.e., the presence of amyloid deposits and Lewy bodies in the neocortex. The identification of α-synuclein peptides in amyloid plaques in DLB brain led to the hypothesis that both peptides mutually interact with each other to facilitate neurodegenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 73 publications
6
67
0
Order By: Relevance
“…In addition, it has also been observed that some amyloidogenic proteins may support cross-seeding by amyloid aggregates of different proteins, building a link between different amyloid forms. Heterologous cross-seeding has been reported between amyloid-β peptide (Aβ) and islet amyloid polypeptide [116,117], Aβ and prion protein (PrP) [118], and Aβ and α-synuclein [119]. Furthermore, Aβ fibrils also induce the formation of tau neurofibrillary tangles in vivo [120], and Aβ aggregates promote tau aggregation in vitro [121].…”
Section: Hetero-amyloid Fibrilsmentioning
confidence: 99%
“…In addition, it has also been observed that some amyloidogenic proteins may support cross-seeding by amyloid aggregates of different proteins, building a link between different amyloid forms. Heterologous cross-seeding has been reported between amyloid-β peptide (Aβ) and islet amyloid polypeptide [116,117], Aβ and prion protein (PrP) [118], and Aβ and α-synuclein [119]. Furthermore, Aβ fibrils also induce the formation of tau neurofibrillary tangles in vivo [120], and Aβ aggregates promote tau aggregation in vitro [121].…”
Section: Hetero-amyloid Fibrilsmentioning
confidence: 99%
“…While many studies have suggested that ␣Syn and A␤ are capable of direct and indirect molecular cross-talks in the brain along with hybrid oligomer formation [21,[174][175][176][177][178][179], few studies have demonstrated that endogenous A␤ and ␣Syn directly interact in cultured cells or in vivo [21]. Specifically, Tsigelny and colleagues reported that ␣Syn and A␤ directly interact in the brains of small (n = 4) groups of patients with AD, DLB and in APP/␣-syn tg mice (Thy1-APPmut tg [line 41] x PDGF␤-␣-syn tg mice [line D]) using co-immunoprecipitation analyses of membrane fractions.…”
Section: Cross-talkmentioning
confidence: 99%
“…Rotenone exposure (as low as 0.5 nM) of neuron cultures from rat hippocampus, substantia nigra and locus coeruleus resulted in the formation of protein aggregates of α-Synuclein and Aβ [56]. Aβ peptides are known to trigger aggregation of α-Synuclein [117], and there is a possibility that heterotypic amyloid co-aggregates could be formed via a α-Synuclein seeding mechanism [118]. Whether such co-aggregations could actually be triggered by any pesticide in cultured neurons or in animal brain remain to be demonstrated.…”
Section: Promotion Of Amyloidogenesismentioning
confidence: 99%